Adolescent Posterior-Superior Glenoid Labral Pathology: Does Involvement of the Biceps Anchor Make a Difference?. Issue 4 (March 2020) - Hansen, Cody H.; Asturias, Alicia M.; Pennock, Andrew T.; Edmonds, Eric W.
Background: Adolescent athletes are at risk of sustaining an injury to the posterior and superior labrum of the glenoid. Limited information is available regarding the outcomes of surgical intervention in this specific age cohort. Purpose: To compare those patients with pure posterior pathology and those with posterior labral tears that involve the biceps anchor (superior labrum anterior-posterior [SLAP] tears) to determine risks for failure in the surgical management. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective review was performed on all patients under the age of 19 years over an 8-year period to identify those treated for superior and posterior labral pathology, followed by chart review, radiographic review, and arthroscopic findings. Patient characteristics and other variables were recorded, including cause (traumatic vs atraumatic), activity/sports (overhead vs nonoverhead), involvement of the biceps anchor—crossing the 12-o'clock position (posterior vs SLAP), associated pathologies, outcome scores (Single Assessment Numerical Evaluation [SANE] and Pediatric/Adolescent Shoulder Survey [PASS] scores), and complications. Results: Forty-eight patients (30 boys, 18 girls) with a mean age at surgery of 16.5 years (range, 13.5-19 years) were identified who met criteria, with a mean follow-up of 4.1 years (range, 1.3-6.9 years). Nineteen patients had SLAP tears and 29 patients had posterior tears. All but 2 regularly participated in sports at the time of their injury; of the athletes, 26 (56.5%) played an overhead sport and 20 (43.5%) played a nonoverhead sport. The cause of the injury was traumatic in 25 cases (52.1%) and atraumatic in 23 cases (47.9%). Outcome scores were not significantly different between cause or type of sports played; SANE scores were not significantly different by tear type (mean SLAP score, 88.4 compared with mean posterior score, 80.9; P = .124); but the mean PASS score in the SLAP group was 88.7, compared with 76.2 in the posterior group ( P = .005) at final assessment. Only 1 SLAP patient had failed management (5.3%) compared with 5 patients in the posterior-only cohort (17.2%). Conclusion: Posterior SLAP tears have better outcomes and lower failure rates than posterior-only tears in the adolescent population. Posterior-superior labral tears can occur in all sports types with multiple causes, but the only factor that appears to play a role in ultimate outcome is whether the tear crosses under the biceps anchor to the anterior side.